2022
DOI: 10.3390/metabo13010053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Linoleic Acid on Cholesterol Levels in a High-Fat Diet-Induced Hypercholesterolemia Rat Model

Abstract: Cardiovascular disease is the leading cause of morbidity and mortality worldwide, accounting for almost one-third of all deaths. The risk factors for developing this disease include high levels of serum total cholesterol (TC), triglycerides (TG), and low-density lipoprotein (LDL), alongside low levels of high-density lipoprotein (HDL). Dietary linoleic acid has been suggested to reduce these risk factors. This study aims to determine the effects of linoleic acid on cholesterol levels, liver function tests, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…In the present study, octadecanoic acid was present in both leaf and callus extracts of V. negundo . The results of the present study were in accordance with reports on Cleistanthus collinus , Goniothalamus umbrosus , Kigelia pinnata , and Melissa officinalis which contained n-hexadecanoic and octadecadienoic acids[ 23 , 24 ]. The study revealed the presence of various bioactive compounds present in all the methanolic extracts of in-vivo and in-vitro plant samples[ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, octadecanoic acid was present in both leaf and callus extracts of V. negundo . The results of the present study were in accordance with reports on Cleistanthus collinus , Goniothalamus umbrosus , Kigelia pinnata , and Melissa officinalis which contained n-hexadecanoic and octadecadienoic acids[ 23 , 24 ]. The study revealed the presence of various bioactive compounds present in all the methanolic extracts of in-vivo and in-vitro plant samples[ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…Hypercholesterolemia, a hallmark of the obese Zucker rat model, was effectively alleviated by HTLE in both lean and obese strains. The observed similar effects in obese rats when co-administered with a Ppar-α ligand and a Cb1 antagonist reinforce that HTLE operates via these two mechanisms simultaneously. ,, Indeed, some other data in the literature also support this perspective. On the one hand, the HTLE structure contains the linoleic acid, which is not only a well-known Ppar-α ligand but also displays a potent effect in reducing hypercholesterolemia as well as the levels of the transaminases AST and ALT in an obesity rat model. ,, On the other hand, Cb1 blockade was also reported to decrease serum levels of total cholesterol in a mouse model .…”
Section: Discussionsupporting
confidence: 55%
“…The observed similar effects in obese rats when co-administered with a Ppar-α ligand and a Cb1 antagonist reinforce that HTLE operates via these two mechanisms simultaneously. 20,48,49 Indeed, some other data in the literature also support this perspective. On the one hand, the HTLE structure contains the linoleic acid, which is not only a wellknown Ppar-α ligand but also displays a potent effect in reducing hypercholesterolemia as well as the levels of the transaminases AST and ALT in an obesity rat model.…”
Section: ■ Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In both animal and human research, OO has been shown to have hypolipidemic effects because it is also high in oleic acid [ 59 ]. Linoleic acid, which has been demonstrated to reduce TC, LDL-C, and VLDL-C levels, is a good source of fat in SO [ 60 ]. On the other hand, CLO is abundant in EPA and DHA, which have been revealed to lower plasma TAG levels.…”
Section: Resultsmentioning
confidence: 99%